TINJAUAN HUKUM BISNIS SYARIAH TERHADAP JUAL BELI ONLINE PADA SITUS TOKOPEDIA.COM - Syulastin Amelia; Zainal Arifin; Fariz Al-Hasni (Universitas Islam Negeri Mataram, 2021)
Tokopedia has a program to support Micro, Small and Medium Enterprises (MSMEs) and individuals to develop their businesses by marketing products online, by providing a 100% money back guarantee if the goods are not sent by the seller (not responsible). The goods listed in the application or official website basically belong to sellers who have officially registered themselves according to the terms and conditions in the tokopedia.com application/site. So, Tokopedia only acts as a third party, in this case as a service provider that carries a market place business model by providing convenience to sellers and buyers in making transactions for buying and selling goods needed by consumers/buyers. The Tokopedia application/site is designed to be very easy so that sellers or buyers are not confused or have difficulty in making transactions for buying and selling goods. Because, the goods listed by the seller on the application or site have been equipped with information regarding the details/specifications of the goods clearly, whether the goods are new or used, with prices that vary depending on the condition of the goods listed by the seller, plus shipping costs (in this case borne by the buyer) which have been calculated automatically by the system from the results of cooperation with various couriers throughout Indonesia.